Analisis Kinerja Simpang Bersinyal Bundaran Tuntung Pandang Kabupaten Tanah Laut - Hafsha Yanti Siregar; Jihan Alya Nabillah (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The increase in population and the growth of motorized vehicles have led to higher traffic volumes at several main intersections, one of which is the Signalized Intersection of Bundaran Tuntung Pandang, which connects the northern approach (Jalan Datu Insyad), southern approach (Jalan A. Syairani), and western approach (Jalan H. Boejasin). This study aims to analyze the performance of the Bundaran Tuntung Pandang signalized intersection using the Indonesian Highway Capacity Manual (MKJI, 1997) and the Indonesian Road Capacity Guidelines (PKJI, 2023). The parameters analyzed include traffic volume, approach capacity, degree of saturation (DS), and level of service (LOS). The results of the analysis show that the northern approach (Jalan Datu Insyad) has the highest degree of saturation (DS) value of 3.460 (LOS F), followed by the southern approach (Jalan A. Syairani) with 3.346 (LOS F), and the western approach (Jalan H. Boejasin) with 2.775 (LOS F). These results indicate that the traffic flow operates at Level of Service F, meaning that the intersection is in a congested condition with unstable traffic flow. Therefore, signal optimization and traffic management strategies are required to improve the intersection’s performance and reduce congestion levels in the area.